Highly active catalyst for CO2 methanation derived from a metal organic framework template. Issue 25 (7th June 2017) - Lippi, R.; Howard, S. C.; Barron, H.; Easton, C. D.; Madsen, I. C.; Waddington, L. J.; Vogt, C.; Hill, M. R.; Sumby, C. J.; Doonan, C. J.; Kennedy, D. F.
Abstract : MOF-derived nanocatalysts activated under reaction conditions display remarkable activity when compared to several controls. Abstract : The conversion of CO2 into chemicals of commercial interest is a rapidly expanding area of research. Here, we present a highly active and stable CO2 methanation catalyst that is derived from a Ru-impregnated zirconium-based metal–organic framework (MOF) material. The Ru-doped MOF is transformed, under reaction conditions, into an active catalyst which yields CO2 conversions of 96% and a CH4 selectivity of 99%. We demonstrate that the final catalyst was composed of a mixture of Ru-nanoparticles supported on monoclinic and tetragonal ZrO2 nanoparticles. Notably, such catalytic activity has only been achieved using the MOF templating strategy. Catalysts of the same composition were synthesized via different methods but were less active for CO2 methanation.